Design response for emergency infectious disease health care facility in the eye of Covid-19: Malaysia's experience - Mohd Nawawi, Norwina; Mustajab, Mumtazah; Zulkarnain, Mustapha Kamal; Md Alwi, Najah; Ismail, Rushdina (UIA-PHG, 2021)
The world was surprised by an unprecedented storm in late January 2020 of an infectious disease like SARs that emerged from Wuhan, Hubei in China-Coronavirus Disease 19 or Covid19. While China locked down their cities and race to build hospitals for the thousands infected, the world was still dumbfounded. Of guard, the disease had arrived on the shores through many gateways -land, sea and air. Suddenly the small incident of the mere three-person from China arriving in Malaysia and soon after Malaysians coming home from holidaying after Chinese New Year and others whom they have contacted along the way were infected at an alarming rate. While the Malaysian hospitals identified as Centres for Infectious Disease (CID) regionally can cope, the concentration of those infected by region and the nature of how the disease was developing was still new, requires new facilities for infectious disease to be on readiness nationwide. The Malaysian Institute of Architects (PAM), through the PAM Committee for Social Responsibility, was approached by Mercy Malaysia to initiate the designs of field hospitals for infectious disease in urgency. However, there was no specific site nor a brief of requirements provided. So how should the institute respond in haste? Can previous knowledge and experience of similar occurrences by the small committee in command assist? This paper aims to share the experiences as architects in a non-government organisation (NGO), i.e. the institute of Malaysian architects-PAM, in readiness to prepare designs of infectious disease facilities for the Malaysian public health care system within the confinement of the Movement Control Order (MCO) period. This paper described and discuss the phenomena as a project management approach to achieve the objectives in the provision of a design brief for the design of a field hospital for infectious disease as a facility in a day and to acquire schematic designs from architects within two days as examples in the decision making process by Malaysian National Security Council (MKN). An explorative method in retrieving data from the phenomena and qualify them with the literature of precedent studies and best practice were adopted, apart from addressing the legitimacy of the process as per the institute and Board of Architects protocol. The brief was to design standalone hospitals for infectious disease that detect the disease; contained it; keep the medical and health staff safe from harm, and able to accommodate those infected within the available resources of the Malaysian health system. The result was seven exemplar ideas contribution from members designed within the 12 hours of launching, meeting the need target of Mercy Malaysia on readiness. It shows that given the grave urgency of the COVID- 19 situations in the country to provide adequate hospital beds, a quick response by the institute has acquired a positive response from the members. The institute may be called for aid after the government has worn off their resources. For better or worse, there are architects in the eye of COVID-19 or any calamity, is ready to serve.